Mitochondrial measures in neuronally enriched extracellular vesicles predict brain and retinal atrophy in multiple sclerosis. (November 2022) - Ladakis, Dimitrios C; Yao, Pamela J; Vreones, Michael; Blommer, Joseph; Kalaitzidis, Grigorios; Sotirchos, Elias S; Fitzgerald, Kathryn C; Saidha, Shiv; Calabresi, Peter A; Kapogiannis, Dimitrios; Bhargava, Pavan
Background: Mitochondrial dysfunction plays an important role in multiple sclerosis (MS) disease progression. Plasma extracellular vesicles are a potential source of novel biomarkers in MS, and some of these are derived from mitochondria and contain functional mitochondrial components. Objective: To evaluate the relationship between levels of mitochondrial complex IV and V activity in neuronally enriched extracellular vesicles (NEVs) and brain and retinal atrophy as assessed using serial magnetic resonance imaging (MRI) and optical coherence tomography (OCT). Methods: Our cohort consisted of 48 people with MS. NEVs were immunocaptured from plasma and mitochondrial complex IV and V activity levels were measured. Subjects underwent OCT every 6 months and brain MRI annually. The associations between baseline mitochondrial complex IV and V activities and brain substructure and retinal thickness changes were estimated utilizing linear mixed-effects models. Results: We found that higher mitochondrial complex IV activity and lower mitochondrial complex V activity levels were significantly associated with faster whole-brain volume atrophy. Similar results were found with other brain substructures and retinal layer atrophy. Conclusion: Our results suggest that mitochondrial measures in circulating NEVs could serve as potential biomarkers of disease progression and provide the rationale for larger follow-up longitudinal studies.